Small at birth : cardiovascular and metabolic health of subjects born SGA and/or preterm and effects of growth hormone treatment - Willemsen, Ruben H (Erasmus Universiteit Rotterdam, 2008)
The doctoral thesis focuses on cardiovascular and metabolic risk factors in children and young adults born SGA and/or preterm and on the effects of GH treatment.
Keywords: velikost těla; Hormone Replacement Therapy; pediatrie; dítě; Growth Hormone; mladý dospělý; poruchy růstu; Adolescent; genetika, lékařská genetika; Body Size; novorozenec nedonošený; Infant, Premature; metabolické nemoci; hormonální substituční terapie; Risk Factors; Cardiovascular Diseases; Young Adult; Metabolic Diseases; rizikové faktory; kardiovaskulární nemoci; Growth Disorders; Child; Infant, Small for Gestational Age; embryologie a teratologie; růstový hormon; mladiství; hypotrofický novorozenec